Monetary Integration among Oil Exporter Countries: Testing Kenen’s Product Diversification Hypothesis in the Organization of Islamic Cooperation - Agustiar, Memet (International Journal of Energy Economics and Policy, 2020)
Kene (1969) hypothesizes that countries that are largely dependent on one export commodity could experience weaker monetary integration and synchronize the business cycle among them. This paper aims to retest Kenen’s hypothesis, which is applied to the seven largest oil-producing countries in the Islamic world. This study employs the Optimum Currency Area (OCA) Index and the Pearson correlation matrix to determine the degree of integration and synchronization of the business cycle. This study empirically proves that most oil-producing countries are tightly integrated. Kenen’s hypothesis is less applicable to oil-exporting countries, especially oil countries that have a strong economic structure and higher welfare. This study successfully explains the new empirical finding that homogeneity in the export structure is not bad for monetary integration. Keywords: Monetary integration; Optimum Currency Area; Islamic nations; oil countries. JEL Classifications: E42, F36, F33 DOI: https://doi.org/10.32479/ijeep.8970